New therapeutic approaches for treatment of tularaemia: a review - BOISSET, Sandrine; CASPAR, Yvan; SUTERA, Vivien; MAURIN, Max (Frontiers in Cellular and Infection Microbiology, 2014)
Antibiotic treatment of tularaemia is based on a few drugs, including the fluoroquinolones, the tetracyclines and the aminoglycosides. Because no effective and safe vaccine is currently available, tularaemia prophylaxis following proven exposure to F. tularensis also relies on administration of antibiotics. A number of reasons make it necessary to search for new therapeutic alternatives: the potential toxicity of first-line drugs, especially in children and pregnant women; a high rate of treatment relapses and failures, especially for severe and/or suppurated forms of the disease; and the possible use of antibiotic-resistant strains in the context of a biological threat. This review presents novel therapeutic approaches that have been explored in recent years to improve tularaemia patients’ management and prognosis. First, the activities of newly available antibiotic compounds were evaluated against F. tularensis, including tigecycline (a glycylcycline), ketolides (telithromycin and cethromycin) and fluoroquinolones (moxifloxacin, gatifloxacin, trovafloxacin and grepafloxacin). The liposome delivery of some antibiotics was evaluated. The effect of antimicrobial peptides against F. tularensis was also considered. Other drugs were evaluated for their ability to suppress the intracellular multiplication of F. tularensis. The effects of the modulation of the innate immune response (especially via TLR receptors) on the course of F. tularensis infection were characterized. Another approach was the administration of specific antibodies to induce passive resistance to F. tularensis infection. All of these studies highlight the need to develop new therapeutic strategies to improve the management of patients with tularaemia. Many possibilities exist, some unexplored. Moreover, it is likely that new therapeutic alternatives that are effective against this intracellular pathogen could be, at least partially, extrapolated to other human pathogens.